EFEK PENGHAMBATAN EKSTRAK DAUN WIDURI (CALOTROPIS SP.) TERHADAP CENDAWAN BUSUK BUAH CABAI (COLLETOTRICHUM CAPSICI) - ., Puji Sulaksono , Umrah, Ramadhanil Parhan K. Lamai dan Ramlah Binangkari (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2011)
Inhibitory effect of widuri (Callotropis sp.) leaf extract on Colletotrichum disease of chilli pepper. Inhibitory effect of widuri (Callotropis sp.) leaf extract (WLE) was determined against radial growth, conidial germination, conidial production on red pepper pod lesions and number of lesions formed on the pod. It was found that, compared with control (no WLE), over 50 % radial growth inhibition was recorded 10 days after WLE application at concentrations of 0.5 % or higher. Inhibitions at similar rate were also found on conidial germination 24 hours after WLE application at concentrations of 8 % or higher. WLE at concentrations of 8 % or higher reduced the number of lesion formation up to at least 50 % 8 days after inoculation of the pathogen. At least 50 % reduction in the conidial production was recorded when WLE was applied at concentrations of 4 % or higher.